Piloting Web-Integrated Primal For Beginning Qualitative Researchers through Multidimensional Research Paradigm - BAGAS, Iris S.; LINALCOSO, Shaira T.; ORQUE, Jestoni C.; ABUDA, Ben Fermin Q. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Educational technologies are powerful digital tools that teachers can harness to improve instructional productivity and efficiency to achieve maximum student learning development. This study utilised a multi-dimensional mixed-method research design to validate the researchers’ developed Web-integrated Primal for Beginning Qualitative Researchers. The three phases of this study require two different sets of participants selected through purposive sampling. Senior high school teachers who are fully immersed in teaching Practical Research 1 and 150 students from the two classes of Technical, Vocational, and Livelihood track in Dolores National High School, S.Y. 2021–2022. The data collected were analysed using weighted mean and qualitative response description for phase 1, t-test for independent samples for phase 2, and Colaizzi’s descriptive phenomenological data analysis method for phase 3. The data reveals that the web-integrated primal is highly acceptable in terms of content and relevance and highly acceptable in terms of mechanics. Furthermore, a significant difference in the learning gain scores was manifested between the two groups. This also means that web-integrated primal is more effective in improving the students’ research competence. Lastly, misleading reviews, the unreviewed bulk of manuscripts, and difficulty crafting research topics led the respondents to suggest screening feedback from reviewers, working in groups, and creating pre-identified research categories. Thus, this study concludes that the innovation is acceptable and effective, though there is a need to revisit the guidelines of the web-integrated primal.